THE RELATIONSHIP OF UNDERSTANDING OF ISLAMIC BUSINESS ETHICS AND THE BEHAVIOR OF MUSLIM TRADERS IN THE CONGKO PEOPLE'S MARKET BAREBBO DISTRICT BONE REGENCY - RATIH MUSAHIR; Muh. Hasbi Ash. Shiddiq (Institut Agama Islam Negeri (IAIN) Bone, 2021)
This study discusses the relationship between understanding Islamic business ethics and the behavior of Muslim traders in the Conko People's Market Barebbo District Bone Regency. The purpose of this study was to determine the relationship between understanding Islamic business ethics and the behavior of Muslim traders in Pasar Rakyat Conko Barebbo District Bone Regency and to find out how big the coefficient of determination is for understanding the relationship between understanding Islamic business ethics and the behavior of Muslim women traders in Pasar Rakyat Conko Barebbo District Bone Regency. This study uses a type of field research (Field Research) with a quantitative approach. The number of population and samples in this study were 80 respondents. Data was collected using a questionnaire distributed to each Muslimah trader. The results of the research and discussion show that 1) There is a significant positive relationship between the understanding of Islamic business ethics and the behavior of Muslim traders in the People's Market of Congko Barebbo District Bone Regency from the results of the calculation of the product moment correlation shows ???? !%